Efficiency of different techniques to study the influence of retention time on protein degradation and feed digestibility in the rumen of sheep - Kremer, Roberto (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. (Agric.)) -- University of Stellenbosch, 1983.